(untitled) (Journal of University of Babylon for Engineering Sciences, 2017)
Asphalt pavement influenced by many factors effect on its performance and serviceability, factors like excessive traffic loads, temperatures, water, design and execution mistakes, and lack of maintenance, these make the Pavement has fast deteriorated with time. The temperature in Iraq exceeded the 50o c, and without controlling on traffic loads and no plans in maintenance management lead to appear severity distresses in most of roads in Iraq. Road maintenance management system improvement leads to reduce time and cost and the pavement condition survey is taking a big role in the pavement management at network level provides the information for pavement performance. Three different main roads were selected in the city of Diwaniyah and the distresses amount was surveyed by using two methods: present serviceability rating and pavement condition index to determine the pavement performance. 10 defects were identified in the asphalt pavement out of (19) defects mentioned by the PCI method, the cracks are the densest distresses in the pavement followed by the rutting and potholes and the rest of the distresses are less dense, all of which are due to poor mix design and poorly implemented. The results showed that the users’ opinions of the studied roads were affected mainly by the roads roughness, the PSR values ​​gave a fair rating of the studied roads while the PCI method gave a poor rating that is meaning Iraqis are more bearing to the hardships they face while using the roads. A periodic survey shall be conducted on the transportation network which shall be consisting of a database.